A structure-activity study of fatty acid interaction with mitochondrial uncoupling protein - Jezek, P; Modrianský, M; Garlid, K D (FEBS letters, 1997)
Fatty acid (FA) uniport via mitochondrial uncoupling protein (UcP) was detected fluorometrically with PBFI, potassium-binding benzofuran phthalate and SPQ, 6-methoxy-N-(3-sulfopropyl)-quinolinium, indicating K+ and H+, respectively. The FA structural patterns required for FA flip-flop, UcP-mediated FA uniport, activation of UcP-mediated H+ transport in proteoliposomes, and inhibition of UcP-mediated Cl- uniport by FA, were identical. Positive responses were found exclusively with FA which were able to flip-flop in a protonated form across the membrane and no responses were found with 'inactive' FA lacking the flip-flop ability. The findings support the existence of FA cycling mechanism.
Keywords: Quinolinium Compounds; Protons; liposomy; vztahy mezi strukturou a aktivitou; Fluorometry; Benzoates; chloridy; benzofurany; protony; valinomycin; Benzofurans; Ethers, Cyclic; benzoáty; vazba proteinů; Guanosine Diphosphate; Ionophores; Structure-Activity Relationship; fluorometrie; mastné kyseliny; Fluorescent Dyes; mitochondriální proteiny; Carrier Proteins; Liposomes; guanosindifosfát; Uncoupling Protein 1; ethery cyklické; koncentrace vodíkových iontů; Mitochondrial Proteins; chinolinové sloučeniny; Potassium; Chlorides; Valinomycin; Membrane Proteins; Fatty Acids; membránové proteiny; Biological Transport; transportní proteiny; ionofory; fluorescenční barviva; draslík; iontové kanály; Lauric Acids; biologický transport; Ion Channels; Protein Binding; uncoupling protein 1; Hydrogen-Ion Concentration; kyseliny laurové